Clinical and Procedural Evaluation of a Pharmacy Pharmacokinetic Consult Service. (October 2020) - Chanas, Tyler; Hockman, Rebecca; Rice, Terran; Cox-Hall, Heather; Mallow-Corbett, Stephanie; Alexander, Bryan T.
Purpose: Though previous studies have shown benefit with pharmacist-managed dosing of antibiotics, many institutions still do not offer such services. Our objective was to determine and report novel outcomes associated with the implementation of a pharmacist-managed pharmacokinetic/pharmacodynamic consult service and to assess the impact of direct pharmacist involvement in therapeutic drug monitoring. Methods: Retrospective cohort study of patients who received vancomycin or an aminoglycoside in the medical intensive care unit from January 5, 2013, to January 6, 2015, divided into 2 groups: before/after implementation of the consult service on January 6, 2014. Results: Nine-hundred sixty-two patients were included. Groups were similar at baseline. There were fewer critical values after implementation of the consult service (40.8% vs 27.3%, P < .001). The intervention group had significantly more vancomycin troughs within therapeutic range (15.4% vs 32.8%, P = .019). Time from order entry to medication administration was shorter when pharmacists entered the medication order, although this difference was nonsignificant (103 minutes vs 77 minutes, P = .054). Conclusion: Implementation of a pharmacist-managed dosing and monitoring program led to significantly decreased rates of critical value drug concentrations and increased rates of therapeutic concentrations, with a 25% (NS) decreased time-to-antibiotic administration, therefore demonstrating the additive value of the pharmacist-managed over pharmacist-monitored approach.